Study of three platelet function tests in young adults living in a high altitude city (Cusco, 3399 masl) - Mendoza, Yanet (2019)
Introduction. The variation of hemoglobin in height has been widely studied; to a lesser extent, coagulation in height has been studied. Objective. Determine the values of platelet function tests in residents of a city at high altitude. Methods. An observational study was conducted on 372 university students aged 17 to 29 years, clinically healthy, using non-automated tests. Results. The platelet count had a median of 320000 platelets/mm3. The bleeding time in capillary blood had a median of 1 minute and 30 seconds. 96,8% had retraction of the clot in venous blood. The coagulation time in venous blood had a median of 2 minutes. Conclusion. The assessment of haemostasis in high-altitude residents does not differ from that reported in residents at other altitudes.